Evidence for engrailed-independent wingless autoregulation in Drosophila. - Yoffe, K.B.; Manoukian, A.S.; Wilder, E.L.; Brand, A.H.; Perrimon, N. (Developmental Biology, 1995)
Proper spatial expression of the wingless (wg) gene in the Drosophila embryonic epidermis is crucial to intrasegmental patterning. Single cell wide wg expression is initiated at the blastoderm stage in response to combinatorial regulation by the pair rule genes. Later, during gastrulation, when the epidermal expression of the pair rule genes has disappeared, wg becomes regulated by the activity of the segment polarity genes. The segment polarity gene engrailed (en) is expressed in cells adjacent to the wg-expressing cells and is required to maintain wg transcription. Since wg is in turn required to maintain en expression, wg appears to autoregulate its own expression through an endependent paracrine feedback loop. In this paper, we demonstrate that wild-type wg expression requires wg activity during stage 9, prior to its requirement for en maintenance, indicating that wg has an autoregulatory role that is distinct from its paracrine feedback loop through en. In addition, by misexpressing Wg and En in distinct spatial patterns in the epidermis, we find that En is capable of inducing expression from the endogenous wg gene only in immediate adjacent cells which have been exposed to Wg. Furthermore, exogenous Wg expression enables maintenance of endogenous wg transcription in both wg and en mutant embryos. Our results support the model that in the wild-type embryo, wg has an autoregulatory function which is distinct and separable from paracrine regulation via en. We also provide evidence that late, localized Wg expression is crucial for the asymmetric patterning of epidermal cell types as reflected in the larval cuticle.